Pengaruh Media Diorama Terhadap Keterampilan Menulis Teks Eksplanasi Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas V SD Negeri 20 Pangkalpinang - Lidya Pramita; Romadon; Yorenza Meifinda (Universitas Muhammadiyah Bangka Belitung, 2024)
This study was motivated by students' lack of interest and motivation when learning Indonesian. Apart from that, students had difficulty expressing their ideas in written form, and the results of learning explanatory texts were low. This research aims to determine whether or not diorama media affects explanatory text writing skills. This study employs quantitative research methods with a true experimental design: a two-group pretest and posttest. The sample in this study consisted of 54 students in classes VB and VC. Tests and documentation are the data collection techniques used. The data analysis techniques used are normality tests, homogeneity tests, and hypothesis tests using the independent sample t-test. The results of this research show that diorama media influence the explanatory text-writing skills of fifth-grade students. Judging from the results of the hypothesis test, the sig value is obtained based on the hypothesis test's results. (2-tailed), namely < 0.029 with the Sig (2-tailed) value criteria < 0.005, so it can be said that Ho is rejected and Ha is accepted. Based on this, it can be concluded that diorama media influences the skills of writing explanatory texts in Indonesian language subjects for class V students at SDN 20 Pangkalpinang.